Money Laundering With Financial Technology - Budhi Pratomo, Wisnu; Rivai Zainal, Veithzal; Hakim, Aziz (Cv. Syntax Corporation Indonesia, 2023)
The current pattern of city development is influenced by various aspects, one of which greatly influences the development is the development of the economic sector. The financial services sector, which is one of the pillars of people's lives, has given rise to very rapid development and of course this is what also ends up causing many problems in the financial sector, especially fundamental problems. This research was conducted with a qualitative approach and was descriptive with data collection tools, namely in-depth and gradual interviews. Without synergy between the government, law enforcement agencies, and the community, the potential for money laundering will continue to occur and even massive. Therefore, a short-term solution that can be presented to overcome money laundering in financial technology is the need to optimize regulations governing obligations and prohibitions related to financial Technology systems.